Phoenix - Andrén, Patrik ca. 20. Jh; Söderqvist, Johan 1966- (Verve, 2019)
"From a young age, Jill has acted as the responsible adult in her small family. She cares for her loving but mentally unstable mother and her younger brother. The news that their estranged father will be visiting on Jill's birthday gives the children much needed hope. When the family is struck by tragedy, Jill keeps it a secret." [filmdienst.de]
Original: Norwegen 2018
Bildformat 2.35:1
Specials: Trailer ; hard of hearing subtitles ; audio description
Keywords: Film; DVD-Video